Adaptive Reuse Suggestions in Interior Architecture Education: A Registered Workshop in Ankara - Mine Sungur (Iconarp International Journal of Architecture and Planning)
This study aims to determine both the recommendations for the conservation and reuse of historical buildings in interior architecture education and the learning outcomes of the restoration course. A registered building in Ankara, which formerly served as a production workshop for a vocational high school, has been identified as the study's main issue as it is no longer in use after having served its purpose. As part of the restoration course in this case, senior students in interior architecture department of Selcuk University were asked to submit a variety of function concepts for the registered building. The study focused on both qualitative and quantitative research methods, which included four stages: preparation, analysis, design, and evaluation. Through examples of applications from our nation and around the world, students were given the information they needed to understand the restoration during the first phase, preparation. The second stage, analysis, entails taking measurements of the building's interior and exterior as well as photographing and collecting written and visual records of it. The third step, the design phase, begins with the choice of a new function appropriate for the building's location and style in light of all available data and documentation. The students were asked to assess their level of knowledge regarding conservation and adaptive reuse as well as the learning outcomes of the restoration course before and after taking it in the final stage of the evaluation process, which took place after the fourteen-week restoration course. This study helped interior architecture students gain experience with a holistic design process through an adaptive reuse proposal project. In conclusion, increasing the number of courses on conservation and adaptive reuse in interior architecture education is important in training interior architects who are experts and competent in the field of reuse.